THE ROLE OF MATHEMATICAL METHODS IN THE THEORY OF FINANCIAL INVESTMENTS IN FIXED INCOME - Natalia V. Popova (Вестник Российского экономического университета имени Г. В. Плеханова, 2017)
The article gives the short history of the theory of finance investment with fixed profits in conditions of uncertainty. Special attention is paid to mathematic methods and their role in theory development. The author shows the extension of the mathematic apparatus used in the research as the theory goes on developing. From these points of view some works by the article's author are analyzed. The following conclusions are grounded: the use of mathematic methods plays an important role in shaping and developing the theory, provides an opportunity to systematize market observations, sometimes to explain them and to obtain additional information about investment characteristics of bond.